Using Role Models and Game-Based Learning to Attract Adolescent Girls to STEM - Ioanna Vekiri; Maria Meletiou-Mavrotheris; Oliver Mannay (MDPI AG, 2024)
Various pedagogical approaches have been proposed to attract more female students to STEM (science, technology, engineering, and mathematics), targeting student beliefs and perceptions that are linked to STEM study intentions. The current study, which took place in a secondary school in Cyprus and employed a quasi-experimental design, aims at contributing to this literature. Responses to pre- and post-questionnaires by 69 experimental and 27 control students show that students in the experimental group, who participated in an intervention in which they learned about the lives and accomplishments of STEM/STEAM role models via a game-based learning approach, improved their STEM ability perceptions compared to control group students, who reported similar pre-post survey levels of STEM ability perceptions. Female students benefited more compared to their male counterparts, and using a game-based learning approach contributed significantly to the effectiveness of students' exposure to the role models. Taken together, study findings support the use of role models and learning games as tools to attract more female students to STEM.